Flexural strengthening of reinforced concrete beams using hybrid fibre reinforced engineered cementitious composite. (1st June 2023) - Qasim, M.; Lee, C.K.; Zhang, Y.X.
Highlights: Flexural behaviour of RC beams strengthened with SPH-ECC studied experimentally. Interfacial bond behaviour of SPH-ECC strengthening layers with RC beams analysed. Effects of different strengthening schemes/configurations studied. A FE model for SPH-ECC strengthened RC beams developed and validated. Abstract: In this study, flexural strengthening of reinforced concrete (RC) beams using steel and polyvinyl-alcohol hybrid fibre reinforced engineered cementitious composite (SPH-ECC) with embedded steel reinforcement bars is proposed. The effectiveness of the strengthening was investigated by experimental and numerical studies. The flexural behaviours of one unstrengthened 3500 mm long, 200 mm wide, and 325 mm deep RC beam and three RC beams strengthened with different configurations of 50 mm thick SPH-ECC layer(s) were studied by conducting four-point bending tests. Detailed flexural behaviours in terms of peak load, failure mode, load-deflection curve, cracking patterns, interfacial bond-slip, strain distribution and ductility of the tested beams were studied and compared. Experimental results showed that both the flexural strength of strengthened beams, which were in the range of 125% to 210% of the unstrengthened control beam, and the interfacial bond-slip behaviours between concrete and SPH-ECC was highly depended to the strengthening configuration used. Crack width control ability of the beams was also improved by using SPH-ECC. A finite element (FE) procedure using surface-to-surface cohesive model was also developed to model the flexural behaviours of the strengthened beams. Comparison with experimental results demonstrated that the proposed FE model could accurately predict the flexural behaviours including interfacial bond-slip between the SPH-ECC layers and the RC beam part of the strengthened beams.